2022
DOI: 10.1111/1346-8138.16542
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ultraviolet‐induced melasma formation: A review

Abstract: Melasma, a pigmentation disorder, commonly occurs in exposed skin areas and can be attributed to several factors. Ultraviolet radiation (UVR) is the primary factor that induces and aggravates melasma. Considering gene expression, exposed skin areas experience abnormal gene expression, involving melanin metabolism, oxidative stress, impaired skin barrier function, and abnormal composition of nerve factors. From a histological perspective, UVR can cause basement membrane collapse, melanocyte sinking, and disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Oxidative stress has been linked to compromised epidermal permeability barrier in some cutaneous conditions such as dermatitis and UV irradiation ( Rojo de la Vega et al, 2017 ; Bertino et al, 2020 ; Yang et al, 2022 ). Accordingly, administrations of antioxidants improve epidermal permeability barrier function ( Kuriyama et al, 2002 ; Masaki, 2010 ; Campos et al, 2014 ).…”
Section: Mechanisms By Which Natural Ingredients Improve Epidermal Pe...mentioning
confidence: 99%
“…Oxidative stress has been linked to compromised epidermal permeability barrier in some cutaneous conditions such as dermatitis and UV irradiation ( Rojo de la Vega et al, 2017 ; Bertino et al, 2020 ; Yang et al, 2022 ). Accordingly, administrations of antioxidants improve epidermal permeability barrier function ( Kuriyama et al, 2002 ; Masaki, 2010 ; Campos et al, 2014 ).…”
Section: Mechanisms By Which Natural Ingredients Improve Epidermal Pe...mentioning
confidence: 99%
“…Persons living in the tropical regions of the Americas often develop melasma because of the greater UV radiation. 14 Melasmic pigmentation often diminishes during the winter and increases during the summer or intense sun exposure. One study showed that the use of a broad-spectrum sunscreen can reduce the incidence of melasma by almost 50% during pregnancy.…”
Section: Ultraviolet and Visible Light Exposurementioning
confidence: 99%
“…The skin is directly exposed to UV radiation, thus enduring a heightened ROS load and accumulating more somatic mutations 3,4 . Acute UV exposure results in erythema and skin darkening, while chronic UV exposure leads to skin pigmentation disorders and various signs of photoaging, such as erythema, hyperkeratosis, solar lentigo, melasma, wrinkles and laxity 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…leads to skin pigmentation disorders and various signs of photoaging, such as erythema, hyperkeratosis, solar lentigo, melasma, wrinkles and laxity. [5][6][7] Maintaining stable cellular redox homeostasis is crucial for mitigating the cascade of UV-induced damage at an early stage. This is accomplished through the cellular antioxidant network, which includes enzymatic antioxidants such as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPX) and thioredoxin reductase (TRX), as well as nonenzymatic antioxidants like glutathione (GSH), vitamin C and vitamin E. 2 The tripeptide GSH plays a central role in scavenging ROS, regenerating other antioxidants and acting as a cofactor in the GSH and thioredoxin systems.…”
mentioning
confidence: 99%